2018
DOI: 10.4037/ajcc2018598
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Enteral Feeding, Weight Status, and Mortality in a Medical Intensive Care Unit

Abstract: The finding of a positive association between an order for enteral feeding and survival supports enteral feeding of patients in medical intensive care units. Furthermore, the beneficial effect of enteral feeding appears to apply to patients regardless of body mass index.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 24 publications
2
5
0
5
Order By: Relevance
“…Second, Group I had a significantly lower rate of prokinetic use, possibly indicating improved GI motility. This comes in agreement with pervious evidence that found both trophic feeding and enteral arginine supplementation to be associated with improved GI motility [14][15][16][17][18][19][20][21]. However, although there were no significant differences in the rates of morphine administration, Group II had significantly higher BG avg and rates of norepinephrine use, possibly delaying gastric emptying and increasing their requirement for prokinetics [37].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Second, Group I had a significantly lower rate of prokinetic use, possibly indicating improved GI motility. This comes in agreement with pervious evidence that found both trophic feeding and enteral arginine supplementation to be associated with improved GI motility [14][15][16][17][18][19][20][21]. However, although there were no significant differences in the rates of morphine administration, Group II had significantly higher BG avg and rates of norepinephrine use, possibly delaying gastric emptying and increasing their requirement for prokinetics [37].…”
Section: Discussionsupporting
confidence: 87%
“…PN-associated central line infections and GI associated sepsis) and most other major clinical outcomes [12]. EN, especially in early stage, sustains an intact enteric mucosal barrier by supporting its structural, functional, and immunological elements and prevents dyspiosis which ultimately impedes bacterial translocation and sepsis [13][14][15][16][17][18][19]. Intestinal starvation, with or without PN, has been shown to dramatically increase mucosal permeability and impair mucosal defenses in both animal and human models [20].…”
Section: Introductionmentioning
confidence: 99%
“…These results corroborate those of studies conducted with patients with acute stroke. According to the researchers, the early use of an NGT in intensive care units did not increase the mortality or poor functional outcomes, concluding that this medical device can be safely used with these patients (Kalra et al., 2016 ; Vest et al., 2018 ). In addition, the NGT is the recommended route for early nutrition in patients with reduced levels of consciousness.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown the association between long‐term enteral access devices and early mortality (Johnston et al., 2008 ; Miranda et al., 2019 ; Pih et al., 2018 ) in critically ill patients (Vest et al., 2018 ). In addition, the association between LOS and enterally tube‐fed critically ill patients has also been reported (Anziliero & Beghetto, 2018 ; Atasever et al., 2018 ; Ortega et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation